CONTENT MANAGEMENT SYSTEM ZPRENEUR IN SUPPORT OF ENTREPRENEURSHIP ILEARNING AT PERGURUAN TINGGI RAHARJA - Qurotul Aini; Indri Handayani; Cahyo Anggoro Seto (CCIT Journal, 2015)
Students are not only provided a knowledge of soft skills for studying in lecture bench, but also trained in how to build the entrepreneurial spirits to face the competition of globalization. Each college also has a different method in building students entrepreneurial spirits. In the practice of entrepreneurship courses in Perguruan Tinggi Raharja, the students perform entrepreneurial activity in a way that is still very conventional. Where they are assigned to sell a product within the scope of the campus. Seeing how the conventional sales process and marketing reach is limited, then digagaskanlah an alternative solution to the entrepreneurial activities by utilizing the development of information and communication technology. Zpreneur content management system is a good solution for students perform entrepreneurial activities. Where zpreneur provide a forum for students to sell their products online. Each student can have their own online store on zpreneur system. That way, they can market their products online, and of course develop their market share not only in the scope of the campus.